Chinese Strategy in the Middle East Between Variables & Constants: علوم سياسية - ظفر عبد مطر التميمي, م.د. (lark, 2020)
The discussion of China & its role in the world & the broader Middle East gained important especially , according to the many changes on the world during the period between the end of the twentieth century & the beginning of the twenty-first century, the most prominent of which was the obvious imbalance between the great powers, the collapse of the ( former) Soviet Union, the emergence of some forces trying to impose themselves on the international scene, the accelerating trend towards trade liberalization , globalization of the economy, the state of regional tension & the delayed of the peace process in the broader Middle East .                 With transformation & changes on the map of world powers, China, which is known for its respect for the sovereignty of nations & non-interference in domestic affairs, has sought closer ties of cooperation & partnership with the broader Middle East countries at various levels, economic, political & cultural ,to achieve its current goal of getting rid of the control of one pole on the world order, & set limits to American hegemony over the world . China may not seek to lead the world, or to become the new single pole, but it certainly seeks to limit American influence on the regions of the world, resulting in new balances , maps of power & wealth in the world, thus seek to create & build a state of partnership , alliances with other countries & regions around the world without engaging in any ongoing regional conflicts & tensions through a more pragmatic & balanced strategy in international relations than other global powers.
Keywords: (determinants, geopolitics, investment, strategy, dominance)